ANALISIS PENGARUH METODE PART AND WHOLE TERHADAP HASIL BELAJAR RENANG GAYA BEBAS PADA ANAK USIA 8-12 TAHUN DI FUN SWIMMING ACADEMY - NAPITUPULU, JHON SAMUEL (Kesehatan Olahraga, 2024)
Abstract Swimming is an important skill that children must master for their safety and physical health. Effective teaching methods are crucial to improving student learning outcomes. Free style learning methods cannot be done only by theory but must be done by direct practice on both the water of foot movements, hand movements and breathing. So one of the methods that can be used is the part and whole method. According to Subarjah (2007: 9.11) The part and entire method is a combination of movement of part and the whole, both of the approach in the student to do the movement that has been given for the practice of the whole movement. The "Part and whole" method has been proposed as an effective approach in swimming teaching. The research subjects consisted of 20 students who received independent swimming lessons. This research site is at Fun Swimming Academy Surabaya. This study uses the Class Action Research method that consists of (1) Planning, (2) Action, (3) Observation, and (4) Reflection by performing 2 cycles of action with each cycle having a different training program. The data analysis techniques in this study are qualitative descriptive. The results of the study showed a considerable increase in the value. With an average of 76.90 on the I cycle and 88.10 on the II cycle. And there was an increase of 11.7 on the average, which indicates an improvement in the crawl ability with the part and whole learning method. Keywords : crawl, part and whole method, learning results